Yahoo Answers is shutting down on May 4th, 2021 (Eastern Time) and the Yahoo Answers website is now in read-only mode. **There will be no changes to other Yahoo properties or services, or your Yahoo account.** You can find more information about the Yahoo Answers shutdown and how to download your data on this help page.

# Sin2x/(sinx) - cos2x/(cos x)?

How do u proof that LHS=RHS

### 2 Answers

- 9 years agoFavorite Answer
Since cos^2(x)=(1+cos2x)/2 so we obtain cos2x=2cos^(x)-1 also we know sin2x=2sin(x)cos(x) now if we put these things in what u have writen we will have [(2sin(x)cos(x)]/sin(x) - (2cos^(x)-1)/cos(x) = 2cos(x)-2cos(x)+ (1/cos(x))=sec(x)

Source(s): Me - Sridhar RLv 69 years ago
Only one side of equation is given

any how you can simplify this as follows

sin 2x / sin x - cos 2x / cos x

Taking LCM we get

(sin2x cosx - cos 2x sin x) /sin x cos x

sin(2x -x) / sinx cos x using Sin (A-B) sinAcosB - cosAsinB

sin x/ sin x cos x = 1/cos x

sec x